In between on all levels – [Applied] Foreign Affairs - Mueller, Baerbel (Africana Studia, 2024)
[Applied] Foreign Affairs is a laboratory that investigates spatial, infrastructural, environmental, and cultural phenomena in sub-Saharan Africa. Projects are based on an interdisciplinary, trans-cultural, and experimental approach. Students are introduced to the spatial diversity and cultural vibrancy of contemporary African conditions, followed by “intensives” courses which focus on the status and potential of a specific place or situation, and field work that creates rural growth patterns, urban prototypes, imaginary art spaces, as well as relational physical interventions. Conventional relationships between client, community and architect; studio, university and field are questioned. The process of relating and making is conceptualized in a reactive, slowed-down manner, embracing conditions of uncertainty and fragility. Ideally, spatial and programmatic hybrids of diverse ownerships emerge. While forming [A]FA, I found it problematic that whenever it was about Africa, (northern) schools of architecture either offered highly theoretical seminars on post-colonial theory or very down-to earth design-build studios – often with an uncritical, closeto- neo-colonial approach. The objective of [A]FA has been to work in the spectrum in-between. Keywords: Transdisciplinarity, Design-build, Decolonizing strategies, Transcultural spatial practices.